The English Textbook. Tensions from an Intercultural Perspective (GIST – Education and Learning Research Journal, 2018)
This review article addresses tensions, critiques and trends that are still latent in mainstream research on English textbooks that have looked at their intercultural aspects, which need to be explored from the perspective of critical interculturality to resist the instrumental, regulatory, homogenizing and commercial nature of textbooks developed by foreign and local publishing houses. The manuscript firstly elaborates on the textbook as an object of research; secondly, it discusses critical analysis of the content of textbooks; and thirdly, the text concludes by pondering critical interculturality, as a decolonial alternative, to make possible the construction of criteria of being, knowledge and power to orient the development of the English textbook, and move away from a de-contextualised textbook toward a desirable contextualised one. This article encompasses the state of the art supporting an ongoing research study on the English textbook from the perspective of critical interculturality that is being conducted within the doctoral programme1 in Education at Universidad Pedagógica and Tecnológica de Colombia (UPTC), conducted during 2014-2018, and supported by Universidad Externado de Colombia, Bogotá.            Key words: English textbook, critical analysis, interculturality, critical interculturality1 Decolonising the English Textbook: A Venture from Critical Interculturality
Keywords: English textbook; critical analysis; interculturality; critical interculturality